2018
DOI: 10.1101/350322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated host-pathogen transcriptional dynamics revealed using sorted subpopulations and single,Candida albicansinfected macrophages

Abstract: 13The control of fungal infections depends on interactions with innate immune cells including 14 macrophages, which are among the first host cell types to respond to pathogens such as Candida 15albicans. This fungus is a member of the healthy human microbiome, although also a devastating 16 pathogen in immunocompromised individuals. Consistent with recent findings from studies of other 17 pathogens, we observed that within a population of interacting macrophages and C. albicans, there are 18 distinct host-path… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
(82 reference statements)
2
12
0
Order By: Relevance
“…While C. albicans stimulus promoted signaling processes related to cell survival and migration, or inhibition of ECM synthesis, glucose uptake and metabolism-related processes dominated after C. parapsilosis co-culture. While regulation of EC protective cellular responses seems to be a priority in the case of C. albicans, in line with previous reports (52), regulation of carbohydrate metabolism appears to be a unique characteristic of C. parapsilosis stimulus. In the HSC-activation pathway, the other pathway simultaneously activated by all conditions, both species regulated signaling processes primarily involved in inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…While C. albicans stimulus promoted signaling processes related to cell survival and migration, or inhibition of ECM synthesis, glucose uptake and metabolism-related processes dominated after C. parapsilosis co-culture. While regulation of EC protective cellular responses seems to be a priority in the case of C. albicans, in line with previous reports (52), regulation of carbohydrate metabolism appears to be a unique characteristic of C. parapsilosis stimulus. In the HSC-activation pathway, the other pathway simultaneously activated by all conditions, both species regulated signaling processes primarily involved in inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…Transcription of both challenged and unchallenged macrophages displayed underlying population heterogeneity (Supplemental Figure S3). To identify the transcriptional patterns of genes responding to the spores, we focused on the expression of a subset of genes previously identified as immune response genes (Muñoz et al 2018). Principle component analysis of the aggregated transcriptional data shows there is a clear difference in transcription between macrophages that have and have not been exposed to the fungi (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…This dysbiotic microbiome drove oncogenesis by suppressing macrophage differentiation and T cell activity. Another study found that Candida albicans 's transition from extracellular to intracellular pathogen was accompanied by a coordinated, time-dependent shift in gene expression for both host and fungus (135). These gene expression changes led to a gradual decline in pro-inflammatory cytokine activation by the host immune system.…”
Section: The Immune Response Changes In Response To Pathogen Activitymentioning
confidence: 99%